Advantages and Disadvantages of Partial High Pressure Homogenisation of Milk in Relation to Full-Stream Homogenisation - Katarzyna Ambroziak; Katarzyna Kiełczewska; Dorota Mickiewicz; Aneta Dąbrowska (Polish Journal of Food and Nutrition Sciences)
This study determines the effect of full-stream and partial high pressure homogenisation (constant pressure of 100 MPa, different temperatures: 20 o C, 40 o C, 60 o C) on selected distinguishing features of the colloidal and emulsion phases of milk. The pH values of milk decreased significantly (p<0.05) as a result of full-stream homogenisation, while they remained unaffected by partial homogenisation (p≥0.05). Most of the changes in the titratable acidity and conductivity of milk triggered by full-stream homogenisation and partial homogenisation were not statistically significant (p≥0.05). Partial high pressure homogenisation had a weaker effect on reducing rennet coagulation time and heat stability of milk than the process performed with the full-stream method. Full-stream and partial homogenisation resulted in a statistically significant (p<0.05) reduction in the thermal coagulation time by approx. 44% and 30%, respectively in comparison to the control sample. The values of thermal stability time of milk subjected to full-stream and partial high pressure homogenisation were different (p<0.05). The rennet coagulation time of milk did not differ depending on the homogenisation method applied (p≥0.05). Fat globules size, described by parameters d v 10, d v 50, d v 90, d 32 , and d 43 , was statistically significant (p<0.05) lower upon full-stream homogenisation than upon partial homogenisation. The maximum decrease in d 32 value was 6.5- and 2-fold as a result of full-stream and partial homogenisation, respectively. Microscopic images show that the low effectiveness of partial homogenisation was due to the flocculation of fat globules. Changes to the viscosity of milk as a result of full-stream homogenisation (a decrease) and partial homogenisation (an increase) were noted as well. The advantage of partial high pressure homogenization over full-stream homogenization is the reduction of the influence of the process on the colloidal stability of milk, while the disadvantage is the low efficiency of the process. High pressure homogenization as an innovative method of preservation can be applied in the dairy industry. The desired features of emulsion and colloidal phases, depending on the product, are the result of selection of the method and temperature of the process.